Drawing on walls : a story of Keith Haring - Burgess, Matthew (Enchanted Lion Books, 2020)
Presents the life and work of Keith Haring, a mural artist, detailing his childhood, education, and career. Describes his activism within the LGBTQ+ community and his commitment to sharing art with children around the world. Includes color illustrations.